Pembimbingan Jemaat Di GKSI Isa Almasih Taman Mini Dalam Menolak Politik Uang - Zega, Yanuar Ada; Silaen, Riste Tioma (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2024)
In Indonesia, money politics remains a serious issue, even within religious communities like GKSI Isa Almasih Taman Mini. The impact of money politics not only undermines the integrity of democracy but also erodes the ethical values that religious communities should uphold. The main problem lies in the congregation's lack of awareness and critical understanding of the negative effects of money politics, as well as the weak moral education to reject such practices. This Community Service (PkM) aims to provide guidance and education to the congregation on the dangers of money politics and the importance of maintaining integrity as responsible citizens. This study highlights the vital role of the church in shaping a congregation that is both ethically sound and politically conscious. The PkM was conducted using a participatory approach through interviews, sermons, discussions, and simulations. The uniqueness of this research lies in its holistic approach based on Exodus 23:8, combining spiritual guidance with political education, a method rarely applied within the church context. The results showed an increase in the congregation’s understanding of money politics and their commitment to reject such practices, along with a significant change in their attitudes and actions towards safeguarding the integrity of democracy.Keywords: congregational guidance; monetary politics; political participation; church integrityAbstrakDi Indinesia, politik uang masih menjadi masalah yang cukup serius termasuk dalam komunitas keagamaan seperti di GKSI Isa Almasih Taman Mini. Dampak dari politik uang tidak hanya merusak integritas demokrasi tetapi juga nilai-nilai etika yang seharusnya dipegang teguh oleh umat beragama. Problematika utamanya ialah kurangnya kesadaran dan pemahaman kritis jemaat terhadap dampak negatif politik uang serta lemahnya edukasi moral dalam menolak praktik tersebut. Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk memberikan pembimbingan dan edukasi kepada jemaat tentang bahaya politik uang dan pentingnya menjaga integritas sebagai warga negara yang bertanggung jawab. Penelitian ini menyoroti peran penting gereja dalam membentuk jemaat yang berintegritas dan sadar politik. PkM dilaksanakan dengan metode partisipatif melalui wawancara, khotbah, diskusi, dan simulasi. Keunikan penelitian ini terletak pada pendekatan holistik berbasis Keluaran 23:8, yang menggabungkan pembinaan spiritual dengan edukasi politik, suatu metode yang jarang diterapkan dalam konteks gereja. Hasilnya menunjukkan peningkatan pemahaman jemaat terhadap politik uang dan komitmen mereka untuk menolak praktik tersebut, serta perubahan signifikan dalam sikap dan tindakan jemaat dalam menjaga integritas demokrasi.Kata Kunci: pembimbingan jemaat; politik uang; partisipasi politik; integritas gereja